Solving optimization problems in communications networks using computational intelligence - Shi, Haixiang (2008)
Computational intelligence is an effective method in solving combinatorial optimization problems. We proposed several new models of neural networks based on noisy and chaotic neural networks, by using these methods, NP-hard problems in communication networks (e.g., scheduling, routing, assignment etc.) can be solved in shorter time with better solution quality.